We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
53
1
avatar

https://prnt.sc/pbwlek

 

thank you very much 

 Sep 27, 2019
 #1
avatar+104962 
+2

7y^2  - 4x^2  + 24x + 14y - 57  =  0        rearrange as

 

7y^2  + 14y   - 4x^2 + 24x   =   57         factor  as

 

7(y^2 +2y)  -4(x^2 - 6x)  =  57            complete the square on x and y

 

7(y^2 + 2y + 1) - 4(x^2 -6 + 9)  =  57 + 7 - 36      simplify

 

7(y + 1)^2  - 4(x - 3)^2  =   28          divide through by 28

 

 

(y + 1)^2         (x - 3)^2

_______   -   _________    =      1

      4                  7 

 

 

cool cool cool

 Sep 27, 2019

9 Online Users